(untitled) (Journal of International Studies, 2020)
Researchers are beginning to recognise that organisations often have different levels of market orientation across different aspects of their operations. Focusing on firms involved in export marketing, this study examines how market-oriented behaviour differs across firms’ domestic and export marketing operations. In this respect, the study is the first of its kind since it investigates three main issues: (1) to what extent do differences exist in firms’ levels of market-oriented behaviour in their domestic markets (i.e., their domestic market-oriented behaviour) and in their export markets (i.e., their export market-oriented behaviour), (2) what are the key drivers of such differences, and (3) what are the performance implications for firms of having different levels of domestic and export market-oriented behaviour.